Opętani w teatrze. Zabiegi adaptacyjne na powieści Witolda Gombrowicza w inscenizacji Krzysztofa Garbaczewskiego - Gołos-Dąbrowska, Katarzyna (Załącznik Kulturoznawczy, 2020)
The article constitutes an analysis of Krzysztof Garbaczewski’s performance Possessed based on Witold Gombrowicz’s novel of the same title. The aim of the article is to present the staging that puts Possessed in the context of contemporary humanistic discourses and to reflect on the aesthetic of the performance. The goal is also to analyze the disillusioning tricks used by the director, to point out the convention plays presented in the spectacle and to illustrate the self-referential function of the stage space. The text also outlines the director’s adaptation strategy and the use of narration in the staging.